EXPLORING THE MODERATING EFFECTS OF RELATIONSHIP INERTIA AND SWITCHING COST ON CR M PERFORMANCE-CUSTOMER SATISFACTION- RETENTION LINK: EMPIRICAL EVIDENCE FROM INDIAN BANKING INDUSTRY - Arup Kumar Baksi and Bivraj Bhusan Parida (Abhigyan, 2013)
Customer relationship management (CRM) has transformed the relationship between a buyer and a seller, particularly in intangible business transactions (service industry). It’s high time that impact of CRM performance on customer satisfaction-retention link should be assessed. The purpose of this paper is to propose and justify a customer satisfaction - customer retention model in a CRM ecosystem with an insight into the probable moderating impact of relationship inertia and switching cost. The study was carried out on the State Bank of India involving certain specific branches in southern part of West Bengal, India. Multivariate statistical procedures were applied which included a double regression analysis and exploratory and confirmatory factor analysis followed by structural equation modeling to justify the factor constructs of the proposed model. The study revealed a positive link between CRM performance, customer satisfaction and retention with relationship inertia and perceived switching costs significantly influencing the link between the three major variables.